Regional Expression of npy mRNA Paralogs in the Brain of Atlantic Salmon (Salmo salar, L.) and Response to Fasting - Tolås, Ingvill; Kalananthan, Tharmini; Gomes, Ana S.; Lai, Floriana; Norland, Sissel; Murashita, Koji; Rønnestad, Ivar (Frontiers in Physiology, 2021)
Neuropeptide Y (NPY) is known as a potent orexigenic signal in vertebrates, but its role in Atlantic salmon has not yet been fully established. In this study, we identified three npy paralogs, named npya1, npya2 and npyb, in the Atlantic salmon genome. In silico analysis revealed that these genes are well conserved across the vertebrate’s lineage and the mature peptide sequences shared at least 77% of identity with the human homologue. We analyzed mRNA expression of npy paralogs in eight brain regions of Atlantic salmon post-smolt, and the effect of 4 days of fasting on the npy expression level. Results show that npya1 was the most abundant paralog, and was predominantly expressed in the telencephalon, followed by the midbrain and olfactory bulb. npya2 mRNA was highly abundant in hypothalamus and midbrain, while npyb was found to be highest expressed in the telencephalon, with low mRNA expression levels detected in all the other brain regions. 4 days of fasting resulted in a significant (p<0.05) decrease of npya1 mRNA expression in the olfactory bulb, increased npya2 mRNA expression in the midbrain and decreased npyb mRNA expression in the pituitary. In the hypothalamus, the vertebrate appetite center, expression of the npy paralogs was not significantly affected by feeding status. However, we observed a trend of increased npya2 mRNA expression (p=0.099) following 4 days of fasting. Altogether, our findings provide a solid basis for further research on appetite and energy metabolism in Atlantic salmon.